2015
DOI: 10.1038/tp.2015.180
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome system dysregulation and treatment resistance mechanisms in major depressive disorder

Abstract: Several studies have demonstrated that allelic variants related to inflammation and the immune system may increase the risk for major depressive disorder (MDD) and reduce patient responsiveness to antidepressant treatment. Proteasomes are fundamental complexes that contribute to the regulation of T-cell function. Only one study has shown a putative role of proteasomal PSMA7, PSMD9 and PSMD13 genes in the susceptibility to an antidepressant response, and sparse data are available regarding the potential alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…In that study, in peripheral blood cells and fibroblasts collected from patients, the proteasome was shown to be responsible for the degradation of proteins and to control autoimmune disorders and immune tolerance. These functions are also relevant to disorders of the digestive system (Minelli et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, in peripheral blood cells and fibroblasts collected from patients, the proteasome was shown to be responsible for the degradation of proteins and to control autoimmune disorders and immune tolerance. These functions are also relevant to disorders of the digestive system (Minelli et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Zheng et al investigated the high sensibility of salivary exosomal PSMA7 on IBD diagnosis [121]. This study identified the proteins within EVs by using a liquid chromatograph-mass spectrometer, and PSMA7 was shown to be associated with inflammation and immune response as well as depressive disorder in many studies [122,123]. Rab proteins of the GTPase family are involved in selective packaging and docking at the plasma membranes of EVs [124].…”
Section: Clinical Potential Of Evs As Biomarkersmentioning
confidence: 99%
“…To the best of our knowledge, only one study deals with AD response in HDF from AD-responder patients as compared to AD-resistant patients (defined as the failure to respond to two or more different classes of ADs and to a tricyclic AD drugs) [ 50 ]. They used HDF from a subpopulation of their cohort to study the link between PSMD13 ( gene encoding a key protein in the ubiquitin-proteasome complex) polymorphism (rs3817629) and the cognate mRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…They used HDF from a subpopulation of their cohort to study the link between PSMD13 ( gene encoding a key protein in the ubiquitin-proteasome complex) polymorphism (rs3817629) and the cognate mRNA expression. They showed that the double homozygous recessive GG carrier gene patients (4%) present a greater risk of AD resistance and have a diminished PSMD13 mRNA expression in HDF [ 50 ].…”
Section: Resultsmentioning
confidence: 99%